Role of IL-6 and IGF-1 in sarcopenia - Nur Riviati; Legiran Legiran; Taufik Indrajaya; Irsan Saleh (Universitas Aisyah Pringsewu, 2023)
Background: Sarcopenia is a syndrome characterized by decreased muscle mass and decreased muscle strength and muscle function. Oxidative stress and inflammatory processes are known to contribute to sarcopenia by releasing the catabolic stimuli interleukin-6 (IL-6) and insulin-like growth factor (IGF). Methods: The method used is a literature review by collecting appropriate articles from the PubMed and Google Scholar databases. Results: Low IL-6 can trigger satellite cell activity and myotube regeneration, whereas if IL-6 production increases chronically, it triggers muscle wasting. Changes in muscle size are the result of changes in the synthesis and degradation of muscle protein. IGF-1, where signal changes are strongly related to muscle size. IGF-1 binding to the receptor causes intracellular phosphorylation of the adapter protein Shc or insulin receptor substrate (IRS-1). Conclusion: The role of IGF-1 and IL-6 can be helpful as diagnostic and prognostic parameters for sarcopenia. Abstrak: Latar belakang: Sarkopenia adalah sindrom yang ditandai dengan penurunan massa otot disertai penurunan kekuatan otot dan atau fungsi otot. Stres oksidatif dan proses inflamasi dikenal sebagai faktor pemicu untuk sarkopenia dengan melepaskan rangsangan katabolik interleukin-6 (IL-6) dan IGF1. Metode: Metode yang digunakan adalah literature review dengan mengumpulkan artikel-artikel yang sesuai dari data base PubMed dan google sholar. Hasil: IL-6 yang rendah dapat mencetuskan aktivitas sel-sel satelit dan regenerasi myotube, sedangkan bila produksi IL-6 meningkat secara kronik mencetuskan muscle wasting. Perubahan ukuran otot merupakan dampak dari perubahan sintesis dan degradasi protein otot. IGF-1 dimana perubahan sinyal berhubungan kuat dengan ukuran otot. Ikatan IGF-1 pada reseptor menyebabkan fosforilasi intracellular adaptor proteins Shc atau insulin receptor substrate (IRS-1). Kesimpulan: Peran IGF-1 dan IL-6 dapat berguna sebagai parameter diagnostik dan prognostic terhadap kejadian sarcopenia.